Updated DEGUM Quality Requirements for the Basic Prenatal Screening Ultrasound Examination (DEGUM Level I) between 18 + 0 and 21 + 6 weeks of gestation - Kähler, Christiane; Schramm, Thomas; Bald, Rainer; Gembruch, Ulrich; Merz, Eberhard; Eichhorn, Karl-Heinz (Ultraschall in der Medizin - European Journal of Ultrasound, 2020)
A precondition for the early detection of fetal abnormalities is the high quality of prenatal basic ultrasound (screening examination). The objective of ultrasound screening is the recognition of abnormal fetal growth and fetal anatomical anomalies. The prenatal detection of fetal abnormalities enables detailed prenatal counselling of parents, improved care at birth and potentially a reduction in morbidity and mortality. In the guidelines for maternity care in Germany (“Mutterschaftsrichtlinien”), the performance of basic ultrasound in pregnancy is not clearly defined. The required image documentation includes a few biometric measurements only. Therefore, adherence to a standard technique and the possibility of audit are limited, thus not necessarily resulting in high screening quality. In this update of the DEGUM quality requirements for level I screening ultrasound examination between 18 + 0 and 21 + 6 weeks of gestation, the required parameters, standard planes and required documentation are described in detail. The greater experience of gynecologists in the field of sonographic screening examinations and the use of a modern ultrasound technique allow improvement of the screening quality. This will improve the standard of basic ultrasound screening. Due to the enhanced standard of the DEGUM I examination, more pregnant women may benefit from a detailed ultrasound examination and specialized therapy in DEGUM level II and III centers. The required fetal structures are described in detail. This update of the requirements for level I DEGUM basic ultrasound examination between 18 + 0 and 21 + 6 weeks of gestation goes far beyond the guidelines for maternity care in Germany (the “Mutterschaftsrichtlinien”) thereby elevating standards.
Keywords: prenatal diagnosis; second trimester; level I examination; quality requirements